Growing underground: Development of thermogenesis in pups of the fossorial rodent Ctenomys talarum - Luna, Facundo; Sastre-Serra, Jorge; Oliver, Jordi; Antenucci, C. Daniel (Frontiers in Ecology and Evolution, 2023)
In mammals, during pup´s development and adult life, integrated requirements of all activities of the individual must conform to a sustained rate of metabolism. Thus, partitioning the available energy according to short-term priorities in a specific moment that allows animals to survive and optimize long-term reproductive success. In altricial rodents, thermal balance is a key factor for survival. When no exogenous source of heat is present, altricial pups rapidly lose heat reaching ambient temperature (Ta). Fossorial rodents showed a strong dependence on burrows where Ta remains relatively stable within narrow ranges. Pups of the fossorial rodent Ctenomys talarum are altricial, being an excellent model to evaluate the development of thermogenic capacity. In this work, the ontogeny of thermogenic capacity of pups of C. talarum was evaluated. Using respirometry techniques, non-shivering thermogenesis (NST), total thermogenic capacity (cold-induced maximum metabolic rate, MMR) and resting metabolic rate (RMR) in pups until post weaning age (day 60) were analyzed. No NST was present in pups until day 60, Despite the presence molecular markers of NST in brown adipose tissue deposits, becoming functional in adults. Although pups were altricial at birth, they maintain behaviorally their thermal balance during lactation. Total thermogenic capacity became fixed at an early age, indicating an improvement in shivering thermogenesis (ST) efficiency after day 10, which might be related to the development of musculature related to digging. Previous to aboveground dispersal period ( day 60), pups gradually reach adults Tb by improving ST and thermal isolation, allowing them to confront climatic fluctuations on surface.